Does Religiosity Mediate Suicidal Tendencies? A South African Study of Muslim Tertiary Students - Kazi, Tasnim Bibi; Naidoo, Sarojini (2016)
Despite international studies into religion’s protective mechanism against suicidal tendencies, within South Africa there is a paucity of research investigating this relationship. This quantitative study investigates the relationship between religiosity and suicidal tendencies in a sample of Muslim students (N = 111). Two scales were used to test the hypothesis that religion mediates suicidal tendency: the Religious Orientation Test and the Multi-Attitude Suicide Tendency Scale. The findings confirmed this hypothesis but disconfirmed our second hypothesis that there would be gender differences between the variables. We concluded that a high degree of religiosity acts as a protective mechanism against suicidal tendencies and discuss the implications of our findings.
Keywords: Suicidal tendency; Religiosity; Muslim; South Africa